2010
DOI: 10.1246/cl.2011.58
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Solid-state Optical Properties of 2,3-Dialkyl- and 2,3,8,9-Tetraalkyltetracenes

Abstract: We prepared 2,3-dialkyl- and 2,3,8,9-tetraalkyltetracenes by way of Diels–Alder reactions between 1,4-anthraquinones and 3,4-dialkylthiophene-1,1-dioxides and obtained mainly orange and yellow solids, respectively. The differences in optical properties in the solid state were probably due to different intermolecular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In contrast to the trisquinones, the tris(tetraceneno)triquinacenes 9 and 10 show the typical structured band shape of higher acenes in the visible region with lowest‐energy transitions at 492 and 512 nm, respectively (Figure 3). The absorption of 9 is close to that of simple 2,3‐dialkyltetracenes 20c. Also, the redshift by Δ$\tilde \nu $ =794 cm −1 for 10 compared with 9 is similar to that reported for 5,12‐diphenyltetracene and parent tetracene (Δ$\tilde \nu $ =770–810 cm −1 , solvent‐depending values) 33a.…”
Section: Resultssupporting
confidence: 77%
“…In contrast to the trisquinones, the tris(tetraceneno)triquinacenes 9 and 10 show the typical structured band shape of higher acenes in the visible region with lowest‐energy transitions at 492 and 512 nm, respectively (Figure 3). The absorption of 9 is close to that of simple 2,3‐dialkyltetracenes 20c. Also, the redshift by Δ$\tilde \nu $ =794 cm −1 for 10 compared with 9 is similar to that reported for 5,12‐diphenyltetracene and parent tetracene (Δ$\tilde \nu $ =770–810 cm −1 , solvent‐depending values) 33a.…”
Section: Resultssupporting
confidence: 77%
“…In a previous fluorescence study involving acene, the fluorescence lifetime was observed to increase because the electronic structure of anthracene and its derivatives was changed when a polar substituent group was attached to the anthracene skeleton . However, when a similar electron-donating group of an alkyl chain was attached to a tetracene core, almost no change in the fluorescence yield was observed because the alkyl chain hardly affected the electronic properties of tetracene . Although the (trialkylsilyl)­ethynyl groups ( 1b , 1c , and 1d ) exhibited similar absorption spectra and HOMO–LUMO properties, their fluorescence yields were observed to differ.…”
Section: Resultsmentioning
confidence: 91%
“…Symmetric tetraalkyl tetracenes 71i–l were obtained by the reaction of dihydroxynaphthoquinone 68d with thiophenedioxides 90a‐d (Scheme ) . The reduction of the adducts 91 followed by treatment with acetic acid led to the formation of anthraquinones 92 , capable of adding another equivalent of thiophenedioxide forming symmetric tetraalkyltetracenes 71i–l upon reduction and acidic work‐up.…”
Section: Cycloaddition To Carbon–carbon Double Bondmentioning
confidence: 99%